2022
DOI: 10.1007/s10551-021-05011-y
|View full text |Cite
|
Sign up to set email alerts
|

Shaming of Tax Evaders: Empirical Evidence on Perceptions of Retributive Justice and Tax Compliance Intentions

Abstract: Although naming-and-shaming (shaming) is a commonly used tax enforcement mechanism, little is known about the efficacy of shaming tax evaders. Through two experiments, this study examines the effects of shaming tax evaders on third-party observers’ perceptions of retributive justice and tax compliance intentions, and whether the salience of persuasion of observers moderates these relationships. Based on insights from defiance theory, the message learning model, and persuasive communications, this study predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 87 publications
0
8
0
2
Order By: Relevance
“…The perception of tax compliance regarded through the e-tax system is explained by tax fairness, but there are also other aspects such as tax complexity and tax knowledge that must be considered (Shafique et al, 2021). An interesting study that connects the economic aspects of tax evaders and the judicial aspects of redistributive justice has been developed by Okafor (2022). The conclusions of this research reveal some important aspects as retributive justice is influenced by shaming punishment; the effects of shaming on the intention of tax compliance are influenced by retributive justice in shaming punishment.…”
Section: Tax Compliance Agendamentioning
confidence: 93%
“…The perception of tax compliance regarded through the e-tax system is explained by tax fairness, but there are also other aspects such as tax complexity and tax knowledge that must be considered (Shafique et al, 2021). An interesting study that connects the economic aspects of tax evaders and the judicial aspects of redistributive justice has been developed by Okafor (2022). The conclusions of this research reveal some important aspects as retributive justice is influenced by shaming punishment; the effects of shaming on the intention of tax compliance are influenced by retributive justice in shaming punishment.…”
Section: Tax Compliance Agendamentioning
confidence: 93%
“…Other scholars have, however, suggested that there should be minimal punitive measures in a tax system to encourage tax compliance (Gberegbe & Umoren, 2017). As an alternative to levying penalties, another method that positively affects the perceptions of retributive justice is the method of naming and shaming the non-compliant taxpayers (Okafor, 2022). The study, therefore, hypothesizes that: H3: There is no association between Fairness and Zimbabwe's digital tax policy.…”
Section: Fairnessmentioning
confidence: 97%
“…This research has been conducted to show that trust in government has a positive effect on compliance (Toniarta & Merkusiwati, 2023). The study by (Okafor, 2023) also stated that high levels of trust in government enable people to pay their taxes voluntarily. Based on the description above, the author formulates the following hypothesis: H2: Trust in Government has a Positive Influence on Compliance…”
Section: The Effect Of Trust Toward Government On Compliancementioning
confidence: 99%
“…Public trust will grow if the government properly realizes the taxes paid. Proof needs to be made by developing infrastructure and the economy (Okafor, 2023).…”
Section: Table 1 Total Of Msme Taxpayers In All Tax Offices In Surabayamentioning
confidence: 99%